The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/su8070649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Smart City Industry on the Korean National Economy: Input-Output Analysis

Abstract: Abstract:The characteristics of the smart city industry and its effects on the national economy of Korea are investigated using input-output analysis. The definition and industrial classification of a smart city are established using the Delphi technique for experts in various fields, from information and communication technologies (ICT) to governmental policies for urban matters. The results of the analysis, including the production, value added and employment induction effects, show that the smart city indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…Kim et al (2016) argued smart city which is one of IT convergence related industry and analyzed demand inducement model and industry linkage effect. They discovered that smart city not only allows sustainable city but also takes an important role in nation's economic growth level [35]. Kim et al (2017) used DDM, SDM and Leontief price Model, as well as the industry linkage effect to analyze the effect of U-healthcare industry that affects Korean economy [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim et al (2016) argued smart city which is one of IT convergence related industry and analyzed demand inducement model and industry linkage effect. They discovered that smart city not only allows sustainable city but also takes an important role in nation's economic growth level [35]. Kim et al (2017) used DDM, SDM and Leontief price Model, as well as the industry linkage effect to analyze the effect of U-healthcare industry that affects Korean economy [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…All these aspects of the emerging smart city phenomenon are consistent with institutional theories; quite surprisingly, however, institutional theories have not been adopted in smart city studies so far. This encourages us to investigate the smart city phenomenon through the lens of institutional logics and organizational fields, rather than other traditional theoretical approaches such as the organizational populations, network organizations or industrial sector views (see for example [77]). …”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
“…Smart city cases in developed countries are different for each region [17], and studies focusing on developing countries have recently shown that smart city development in China [18]- [22], the Middle East [23], [24], and Southeast Asia [25], [26] have adapted various technologies for their new town developments. In addition, research has been conducted in Singapore [25], Australia [27], and South Korea [28], as well as in developing countries such as India [29], [30], some African nations [31], Brazil [32], and others [33]. Such countries are usually in the process of building new cities.…”
Section: A Smart City Literaturementioning
confidence: 99%